Assessment of prevalence and load of torquetenovirus viraemia in a large cohort of healthy blood donors. (October 2020) - Focosi, D.; Spezia, P.G.; Macera, L.; Salvadori, S.; Navarro, D.; Lanza, M.; Antonelli, G.; Pistello, M.; Maggi, F.
Abstract: Objectives: Torquetenovirus (TTV) is an emerging marker of functional immune competence with the potential to predict transplant-related adverse events. A large-scale epidemiological study was performed to understand how basal values vary in healthy individuals according to age and gender. Methods: We tested plasma from 1017 healthy blood donors aged 18–69 years. The presence and load of TTV were determined by a real-time PCR assay. A sub-cohort of 384 donors was tested for anti-cytomegalovirus IgG antibodies, and 100 participants were also tested for TTV viraemia on a paired whole blood sample. Results: The overall prevalence of TTV was 65% (657/1017) with a mean (±SD) growth of 5 ± 4% every 10 years of age increase, but stably higher in males (465/690, 67%) than in females (192/327, 59%). Mean (±SD) TTV load was 2.3 ± 0.7 Log copies/mL with no sex difference. TTV viraemia showed modest increases along 10-year age intervals (mean ± SD: 0.3 ± 0.1). TTV viraemia in donors sampled 2 years later remained stable (mean ± SD: 2.3 ± 0.8 versus 2.2 ± 0.7 Log copies between samples). Twenty-six per cent (9/34) of blood donors with TTV-negative plasma scored positive when whole blood was tested, and the donors with positive plasma showed a mean (±SD) 1.4 ± 0.5 Log increase in copy numbers when whole blood was tested. Conclusions: This study establishes the mean value of TTV viraemia in plasma in healthy blood donors and suggests that ageing causes only minimal increases in TTV viraemia.